Florística das briófitas da Serra dos Carajás e sua possível utilização como indicadoras de metais. - (:unkn) unknown (Museu Paraense Emílio Goeldi, 1995)
The mineral province of Carajás is located in the south of the state of Pará and north of the state of Tocantins. It has about 150,000 K11/ and is influenced by the basins of the Araguaia, Tocantins and Xingu rivers. It presents forested areas (dense forest) and non-forested areas (metallophilous savannas, campo rupestre or canga vegetation). The objectives of this work are to determine the specific diversity of bryophytes in the different ecosystems of Serra dos Carajás and the possible use of some species as indicators of metals. Almost 2000 specimens were collected in the different vegetation types that occur over iron ore (canga), gold (Bahia Project), manganese (Igarapé Azul), copper (Salobo Igarapé) and nickel (Serra Vermelha). As results, 18 families were identified, with Dicranaceae standing out, with the species Campylopus savannarum (C. Mull.) Mitt. occurring abundantly on iron rocks, often associated with Pilosium chlorophyllum (Hornsch.) C. Mull. Mull. Calymperaceae shows the highest specific diversity (9 species). More than 50 species of bryophytes are listed, with their ecosystems, substrates and ores where they occur. Four species were reported for the first time for the State of Pará (CNPq/MPEG, Companhia Vale Do Rio Doce, Fundação Margareth Mee and Fundo Nacional do Meio Ambiente (FNMA)).
Floristics of bryophytes from Serra dos Carajás and their possible use as indicators of metals.
Keywords: Florística; Briófitas; Metais; CNPQ::CIENCIAS BIOLOGICAS::BOTANICA